2012
DOI: 10.1111/j.1525-1594.2012.01553.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of Clinical Propofol Concentrations on Platelet Aggregation

Abstract: The inhibitory effect of propofol on platelet aggregation remains unclear, and studies on the subject disagree. Furthermore, although propofol infusions are widely used for general anesthesia and as sedatives for patients in intensive care units, little information is available on its concentration- and time-related effects on platelet aggregation. Here, the authors investigated the in vitro effect of propofol, at concentrations required for sedation and general anesthesia, on platelet aggregation after 1, 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…The studies in animals [41] and humans [42] indicated that the measured/predicted brain concentration of propofol during maintenance of surgical anesthesia is above 4 µg/ml, and as high as 20 µg/ml [43,44]. Thus, in the in vitro experiments, the doses of propofol used that are within the range of concentrations found in the human brain during surgical anesthesia are referred to as anesthetic doses.…”
Section: Discussionmentioning
confidence: 99%
“…The studies in animals [41] and humans [42] indicated that the measured/predicted brain concentration of propofol during maintenance of surgical anesthesia is above 4 µg/ml, and as high as 20 µg/ml [43,44]. Thus, in the in vitro experiments, the doses of propofol used that are within the range of concentrations found in the human brain during surgical anesthesia are referred to as anesthetic doses.…”
Section: Discussionmentioning
confidence: 99%
“…23 The studies in animals 23 and humans 24, 25 indicated that the measured/predicted brain concentration of propofol during maintenance of surgical anesthesia is above 4 µg/ml, and as high as 20 µg/ml. 26, 27 Thus, in the in vitro experiments, the doses of propofol used that are within the range of concentrations found in the human brain during surgical anesthesia are referred to as anesthetic doses. The concentrations that are outside this range would be called either sub-anesthetic or supra-anesthetic concentrations.…”
Section: Evidence Of Propofol-induced Developmental Neurotoxicitymentioning
confidence: 99%
“…On the other hand, Chung et al observed, that Pro in concentrations required for sedation and general anesthesia had no inhibitory effect on platelet aggregation after 3 h of incubation. 23 …”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 In vitro and ex vivo data suggest that Pro exerts antiplatelet and anti-inflammatory effects. 23 26 Moreover, Pro inhibits platelet thromboxane synthesis and NO production in leukocytes, stimulating the activity of guanyl cyclase in platelets. 27 In our preliminary study, we also observed NO release from endothelial cells, which indicates the significant involvement of endothelium in the effect of Pro on hemostasis.…”
Section: Introductionmentioning
confidence: 99%